Synthesis of Li-doped bismuth oxide nanoplates, Co nanoparticles modification, and good photocatalytic activity toward organic pollutants. Issue 7 (13th September 2020) - Chen, Hongjun; Yu, Chunhu; Xue, Zeyang; Wang, Pengxiang; Wang, Zi; Cong, Qianmin; Pei, Lizhai; Fan, Chuangang
Abstract: Lithium-doped bismuth oxide nanoplates with the thickness of 50–150 nm and tetragonal bismuth oxide, monoclinic lithium bismuthate phases have been synthesized via a simple hydrothermal process using lithium acetate and sodium bismuthate as the raw materials. Cobalt nanoparticles modified lithium-doped bismuth oxide nanoplates hybrids were obtained by an in situ photo-deposition route. The cobalt nanoparticles-modified nanoplates hybrids display significantly enhanced photocatalytic activity toward gentian violet compared with the nanoplates. Gentian violet solution can be totally degraded by the hybrids within 60 min under ultraviolet–visible light irradiation. The superior photocatalytic activity of the cobalt nanoparticles modified nanoplates hybrids originates from the superior charge transfer capacity and the energy band structure of the hybrids. The excellent photocatalytic performance makes the cobalt nanoparticles modified nanoplates hybrids a promising candidate as the photocatalyst for wastewater treatment.